2009
DOI: 10.2967/jnumed.108.059345
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 99mTc-Recombinant Human Annexin V Imaging for Differential Diagnosis of Aseptic Loosening and Low-Grade Infection in Hip and Knee Prostheses

Abstract: The aim of this study was to assess the pattern of annexin V uptake in hip and knee prostheses suspected of being infected. Methods: A total of 7 patients undergoing revision surgery for hip or knee prostheses were studied; 5 patients had total hip replacements, and 2 had total knee replacements. Infection was confirmed by pathology, culture results, laboratory evaluation, and clinical follow-up. All patients also underwent a bone scan before surgery. Results: Annexin V scan findings were positive in 5 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In a preliminary study of seven patients undergoing revision surgery for hip (n05) or knee (n02) prostheses, Lorberboym et al reported for the first time on 99m Tc-recombinant annexin V scintigraphy [93]. They found four true-positive, two true-negative and one falsepositive annexin V images.…”
Section: Investigational/experimental Tracersmentioning
confidence: 96%
See 1 more Smart Citation
“…In a preliminary study of seven patients undergoing revision surgery for hip (n05) or knee (n02) prostheses, Lorberboym et al reported for the first time on 99m Tc-recombinant annexin V scintigraphy [93]. They found four true-positive, two true-negative and one falsepositive annexin V images.…”
Section: Investigational/experimental Tracersmentioning
confidence: 96%
“…Note again, similarly to SPECT/CT, the presence of metal-induced CT artefacts. Performing a PET/CT study was, in this particular case, not contributive uptake in the periprosthetic region is more common and intense in infected prostheses than in aseptic loosening [93].…”
Section: Investigational/experimental Tracersmentioning
confidence: 99%
“…Recently, Mordechai et al [13] reported that in a clinical trial 99m Tc-recombinant human annexin V imaging showed high sensitivity (100%) and low specificity (67%) for diagnosing PJI. The results of our present study improved on this specificity (83.3%).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used for in vivo detection of apoptotic cells in cardiovascular disease and cancer [11] . Other studies using various animal models and human beings have shown that 99m Tc-annexin V can also detect acute, subacute, and chronic infection [9] , [12-13] . In the present study, we investigated whether 99m Tc-annexin V imaging was effective in differentiating early stage PJI from uninfected prosthetic joints in a validated rabbit model [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as shown in Table 3, 99m Tc-Annexin V radiopharmaceuticals have also been used to image patients with diseases such as infection of prostheses, Crohn's disease, glaucoma [3840]. Preliminary clinical data in these patients demonstrated the clinical use of 99m Tc-Annexin V as a diagnostic biomarker for monitoring apoptosis (Figure 2).…”
Section: Radiopharmaceutical and Clinical Trialsmentioning
confidence: 99%